Characteristics of Waste Briquettes Hazelnut Shells with Glutinous Rice Adhesive - Ahmad Akromul Huda; Muliatiningsih; Fathoni, Ahmad; Karyanik (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2023)
The energy crisis is increasingly felt starting from the scarcity of petroleum and gas fuels plus the increasingly expensive price makes it necessary to make efforts to obtain alternative renewable energy. One of the biomass materials that can be used as briquettes is hazelnut shells because in some observations in the field hazelnut shells tend to be discarded after taking the meat. The purpose of this study was to determine the differences in the characteristics of briquettes produced such as moisture content, calorific value, ash content influenced by the type of adhesive derived from glutinous rice so as to obtain the ideal formulation for making briquettes from hazelnut shells. This study used a complete randomised design (CRD) with variations in glutinous rice flour concentration of 20%, 30%, and 40%. The results showed that the concentration of the adhesive used was not significantly different from the value of water content, ash content and calorific value produced. The best quality briquettes were at 40% adhesive percentage, with a calorific value of 5321 cal/gr, 7.2% moisture content, and 5.1% ash content. Pecan shell briquettes with rice flour adhesive are in accordance with the Indonesian national standard (SNI) both from the value of water content, ash content and calorific value.